2020
DOI: 10.1038/s41598-020-60541-1
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Zinc Oxide Nanoparticles Using Aqueous Extract of Deverra tortuosa and their Cytotoxic Activities

Abstract: in recent years, there is a growing interest towards the green synthesis of metal nanoparticles, particularly from plants; however, yet no published study on the synthesis of Zno.nps using the Deverra tortuosa extract. through this study, zinc oxide nanoparticles (Zno.nps) have been synthesized based on using the environmentally benign extract of the aerial parts of D. tortuosa as a reducing and capping agent. ZnO.NPs synthesis was confirmed using UV-Visible (UV-Vis) spectroscopy, Fourier Transform Infrared Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
138
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(185 citation statements)
references
References 39 publications
13
138
0
1
Order By: Relevance
“…This variation could be attributed to a difference in the amount of ZnO NPs or changes in cell density [ 55 ]. The results obtained herein are consistent with the previous studies that reported significant cytotoxicity of ZnO NPs to human hepatocellular carcinoma HepG2 [ 56 , 57 ], bronchial epithelial BEAS-2B , lung adenocarcinoma A549 [ 58 ], colon adenocarcinoma Caco-2 [ 20 ], breast MCF-7 and MDA [ 59 ] cancer cells.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This variation could be attributed to a difference in the amount of ZnO NPs or changes in cell density [ 55 ]. The results obtained herein are consistent with the previous studies that reported significant cytotoxicity of ZnO NPs to human hepatocellular carcinoma HepG2 [ 56 , 57 ], bronchial epithelial BEAS-2B , lung adenocarcinoma A549 [ 58 ], colon adenocarcinoma Caco-2 [ 20 ], breast MCF-7 and MDA [ 59 ] cancer cells.…”
Section: Resultssupporting
confidence: 92%
“…This results in a change in the surface of the NPs by elevating a variety of electrons and holes, followed by the generation of ROS and oxidative stress, which eventually cause the death of cells. However, the anti-oxidative capability of the cell is surpassed; thus, ZnO NPs would act as a redox system [ 20 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, plants produce more various nanoparticles, either in shape or in size. [1][2][3][4][5][6] The nanoparticles have broad-spectrum applications in health care, cosmetics, biomedical food and feed, drug/ gene delivery, environmental studies, mechanics, optics, light limiters, nonlinear optical and photoelectron chemical applications, and that rely on the different synthesis processes. In UV-visibleregions, the versatile semiconductor behavior, their momentous optical transparency and luminescent properties and their applications in solar cells, ceramics, and catalysts, cosmetics, gas sensors, and lighting arrestors.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced from[143] under the Creative Commons Attribution.4.1.2. Cancerous CellsNano-ZnO materials have been reported to attack multiple cancer cell lines based on cytotoxic assay results[50,126,[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162]. Very recently, Hussain et al synthesized spherical ZnO NPs (90 nm) from Pandanus odorifer leaf extract and zinc acetate dihydrate.…”
mentioning
confidence: 99%